Nigeria's Non-Oil Exports : Determinants of Supply and Demand, 1970-1990 - Lukonga, Inutu (IMF Working Papers; Working Paper ;, 1994)
This paper reviews Nigeria's non-oil export performance during the period 1970-90, analyzes the factors underlying the dismal performance, and estimates the supply-price elasticity of the exports for both the short and long run. A distinguishing feature of the analysis is the incorporation of the effect of domestic demand in the export supply equation for agricultural commodity exports--a feature usually reserved for the manufactured goods where it is generally assumed that domestic demand competes with export demand. The results provide evidence of the adverse effects of restrictive government policies on exports and underscore the utility of pricing policy in eliciting export supply.